Study Technology: The Suitable Tenacity to Learning Snags - Amos Ochayi ONOJAH; Adenike Aderogba ONOJAH; Charles Olubode OLUMORIN; Isaac Olakanmi ABIMBOLA (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
Study technology is a student-centered learning technique that helps the learner to study successfully by providing solutions to all barricades come upon in the progression of studying. This study designed a model on study technology with the barriers that hinder students from studying effectively, the psychological reactions as well as the solutions to the barriers. The study is a position paper which directs the author to review some materials. The findings established that the major barriers to successful study are absence of mass, misunderstood words, obscurity and skipping gradient. In addition, the proffered solutions to the barriers include use of learning materials, use of dictionary, applying mnemonics and adopting a systematic learning style. The study concluded that with study technology, 100% performance is achievable. It was however recommended that students at all levels should assist themselves by adopting the study technology principles.